2015
DOI: 10.1016/j.jtcvs.2015.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Graft flow assessment using a transit time flow meter in fractional flow reserve–guided coronary artery bypass surgery

Abstract: As coronary stenosis severity increased, graft flow increased, pulsatility index decreased, and proportion of patients with systolic reverse flow increased. In mild coronary artery stenosis, the chance of flow competition between the native coronary artery and the bypass graft increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 12 publications
1
57
1
3
Order By: Relevance
“…In a recent review of published TTFM studies, Niclauss et al concluded that the mean graft flow positively predicts long‐term patency (minimum threshold of 20 mL/min for IMA grafts and 30‐40 mL/min for vein grafts) . Coronary artery bypass graft failure has been associated with the following: high fractional flow reserve (FFR) (which was also associated with high mean PI, probably due to competitive, antegrade flow from the native coronary artery); TTFM measurements in the early diastolic phase; smoothness of the graft‐flow curve for arterial grafts; and high PI and high systolic reverse flow . Published work from our group has shown that differences of TTFM parameters between left‐ and right‐sided vein grafts were small and unlikely to be of clinical relevance …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review of published TTFM studies, Niclauss et al concluded that the mean graft flow positively predicts long‐term patency (minimum threshold of 20 mL/min for IMA grafts and 30‐40 mL/min for vein grafts) . Coronary artery bypass graft failure has been associated with the following: high fractional flow reserve (FFR) (which was also associated with high mean PI, probably due to competitive, antegrade flow from the native coronary artery); TTFM measurements in the early diastolic phase; smoothness of the graft‐flow curve for arterial grafts; and high PI and high systolic reverse flow . Published work from our group has shown that differences of TTFM parameters between left‐ and right‐sided vein grafts were small and unlikely to be of clinical relevance …”
Section: Discussionmentioning
confidence: 99%
“…Graft failure is generally associated with the severity of the proximal stenosis, which in turn affects competitive flow from native vessels, other bypass grafts or collateral vessels, and the quality of the grafted vessel and tandem myocardium perfused by the grafted vessel . Differences between microvascular health and microvascular disease, as described by Gutterman et al may also play a fundamental role.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, attenuated disturbed flow with stagnation appeared in the inlet vessel wall of the diffuser model. However, this flow pattern in the inlet vessel is absent in the coronary artery in vivo . The aforementioned velocity and flow profiles are visualized with heatmap colors (Figure e; Video S4, Supporting Information).…”
mentioning
confidence: 99%
“…Finally it's important to mention that fractional flow reserve measurement preoperatively along with real-time graft flow assessment using epigraftic ultrasonography perioperatively is pivotal for assuring long-term patency of the grafts (26,27). Unfortunately, none of these tests are routinely used in everyday practice.…”
Section: Concernsmentioning
confidence: 99%